Pengaruh Kompetensi, Motivasi Dan Disiplin Terhadap Kinerja Guru SMP Negeri 15 Malang - Suwaiba, Suwaiba; Graha, Andi Nu; Wilujeng, Sri (Reflection Journal, 2026)
Teacher performance is a key factor in determining the quality of national education, as teachers function not only as knowledge providers but also as facilitators, motivators, and character builders for students. However, observations indicate that teacher performance remains suboptimal, particularly in learning innovation, discipline consistency, and work motivation. This study aims to analyze the influence of competence (X1), motivation (X2), and discipline (X3) on teacher performance (Y) at SMP Negeri 15 Malang, both simultaneously and partially. A quantitative survey method with saturated sampling was applied, involving 46 teachers. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed through multiple linear regression with SPSS. The results show that competence, motivation, and discipline simultaneously and partially have a significant effect on teacher performance. The Adjusted R Square value of 0.632 indicates that 63.2% of teacher performance variation is explained by these variables. The regression equation obtained is Y = 12.644 + 0.589X1 + 0.066X2 + 0.130X3. Improving teacher performance requires strengthening competence, motivation, and discipline in an integrated manner.